ANALISIS SEJARAH DAN PENDEKATAN SENTRALISASI DALAM PENGELOLAAN TAMAN NASIONAL BALI BARAT - Amir Mahmud; Arif Satria; Rilus A Kinseng (Jurnal Analisis Kebijakan Kehutanan, 2015)
Management of natural resources especially for conservation area is still under control of central government, although provincial and regent governments have limited role/authority in the decentralization era. The research aims to analyze the historical evolution of Bali Barat National Park (TNBB) and its management. The results show that the TNBB was originally from wildlife reserve and management of TNBB conservation under the authority of the Ministry of Forestry (MoF) at central government. In the desentralization era, provincial and regent government have role/authority such as in national park planning. Also in that era, people can utilize resources in conservation areas for tourism development, and provide traditional zone for fishermen. For fishermen, the TNBB zoning in 2010 is far better than the previous zoning.